Teenage Pregnancies: Risk Factors and Associated Neonatal Outcomes in an Eastern-European Academic Perinatal Care Center - Suciu, Laura Mihaela; Pasc, Andrada Larisa; Cucerea, Manuela; Bell, Edward F. (American Journal of Perinatology, 2016)
Objectives This study aims to compare women with early (13–16 years), late teenage (17–19 years), and adult (25–29 years) pregnancies regarding pregnancy risk factors and reproductive outcomes.Methods An observational study, utilizing medical charts and direct interview, conducted in an academic hospital during January 2011 and December 2012. Our sample comprised 395 teenage and 736 adult pregnancies.Results Pregnant teenagers were more likely than adults to be single (41.7 vs. 33.2%; odds ratio [OR]: 1.43, 95% confidence interval [CI]: 1.11–1.84), to live in a rural area (70.9 vs. 53.9%; OR: 2.07, 95% CI: 1.60–2.69), and to live with extended family (74.2 vs. 16.0%; OR: 15.04, 95% CI: 11.15–20.29). Adolescent mothers were more likely than adult mothers to give birth by vaginal delivery (78.5 vs. 69.6%; OR: 1.82, 95% CI: 1.17–2.84), and rate of operative delivery was lower amongst this group (8.6 vs. 9.8%; OR: 0.8, 95% CI: 0.5–1.3). The newborns of adolescent mothers were more likely to be low birth weight (14.9 vs. 9.1%; OR: 1.75, 95% CI: 1.20–2.54) and more likely to successfully breastfeed (91.9 vs. 82.2%; OR: 2.45; 95% CI: 1.63–3.69) but the length of hospital stay was similar with adult mothers' newborns.Conclusions The distinct risk factors and behaviors associated with pregnancy, among teenagers may help address the health needs of this unique and vulnerable group and their offspring.
Keywords: EU countries; teenage; pregnancy; neonatal outcomes